2006
DOI: 10.1136/oem.2005.025122
|View full text |Cite
|
Sign up to set email alerts
|

Why are manual workers at high risk of upper limb disorders? The role of physical work factors in a random sample of workers in France (the Pays de la Loire study)

Abstract: In working men and women, upper limb musculoskeletal disorders are frequent. Physical work exposures, such as repetitive and forceful movements, are an important source of risk and in particular account for a large proportion of excess morbidity among manual workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
83
0
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(93 citation statements)
references
References 24 publications
4
83
0
6
Order By: Relevance
“…Physical and psychological job demands influence our health, wellbeing, and longevity in many ways (1,2). Physical job demands, such as repetitive movements, awkward posture, and pace have been associated with morbidity (3)(4)(5), disability retirement (6), and even mortality (7,8). According to recent Finnish research, a fourth of employees rate their work as physically demanding (9).…”
mentioning
confidence: 99%
“…Physical and psychological job demands influence our health, wellbeing, and longevity in many ways (1,2). Physical job demands, such as repetitive movements, awkward posture, and pace have been associated with morbidity (3)(4)(5), disability retirement (6), and even mortality (7,8). According to recent Finnish research, a fourth of employees rate their work as physically demanding (9).…”
mentioning
confidence: 99%
“…A few studies have indicated that occupational factors contribute to socioeconomic disparities in musculoskeletal disorders in general (8,(17)(18)(19). Physical and psychosocial work characteristics accounted for a substantial part of the relation between socioeconomic status and musculoskeletal complaints in men who graduated from high school in Wisconsin (8).…”
mentioning
confidence: 99%
“…fatigue, stress, substance use, occupational injuries, disabilities 2,3,5,9,10,12,18,19) , and death 20) . The role of physical job demands is little documented.…”
mentioning
confidence: 99%